Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Solve the system of equations:

[tex]\[
\begin{cases}
x + 2y = 12 \\
y = -3x + 11
\end{cases}
\][/tex]


Sagot :

Certainly! Let's solve this system of linear equations step by step:

We have the following system of equations:
[tex]\[ \begin{cases} x + 2y = 12 \\ y = -3x + 11 \end{cases} \][/tex]

Step 1: Substitute the second equation into the first equation

We know from the second equation that [tex]\( y = -3x + 11 \)[/tex]. We can substitute this expression for [tex]\( y \)[/tex] in the first equation:

[tex]\[ x + 2(-3x + 11) = 12 \][/tex]

Step 2: Simplify the equation

Distribute the 2 into the expression [tex]\(-3x + 11\)[/tex]:

[tex]\[ x - 6x + 22 = 12 \][/tex]

Combine like terms:

[tex]\[ -5x + 22 = 12 \][/tex]

Step 3: Solve for [tex]\( x \)[/tex]

Isolate [tex]\( x \)[/tex] by subtracting 22 from both sides:

[tex]\[ -5x = 12 - 22 \][/tex]

[tex]\[ -5x = -10 \][/tex]

Divide both sides by -5:

[tex]\[ x = 2 \][/tex]

Step 4: Solve for [tex]\( y \)[/tex]

Use the value of [tex]\( x \)[/tex] that we found to determine [tex]\( y \)[/tex]. Substitute [tex]\( x = 2 \)[/tex] back into the second original equation [tex]\( y = -3x + 11 \)[/tex]:

[tex]\[ y = -3(2) + 11 \][/tex]

Simplify:

[tex]\[ y = -6 + 11 \][/tex]

[tex]\[ y = 5 \][/tex]

Solution:

The solution to the system of equations is:

[tex]\[ (x, y) = (2, 5) \][/tex]